Silicon isotope variations accompanying basalt weathering in Iceland - Georg, R; Reynolds, B; West, A; Burton, K; Halliday, A (2007)
This study presents the Si isotope compositions of the dissolved phase of twenty rivers from across Iceland. The high-resolution Nu Plasma 1700 MC-ICP-MS was used to provide interference-free 30Si/28Si ratios with an average limiting precision of ± 0.04‰ δ30Si. The Si isotope composition ranges from - 0.08‰ to 1.46‰ δ30Si, averaging 0.63 ± 0.38‰ (± 1σSD). This is only slightly lighter than the recently reported mean of 0.84 ± 0.19‰ for high precision measurements of Swiss rivers but is significantly lighter than compositions reported for some other rivers. The Si isotope composition varies slightly with the amount of glacial cover, which provides evidence that the continental Si input to the oceans may be climatically controlled and thus likely to vary over glacial-interglacial cycles. After correction for the dissolution of trace amounts of calcite in one region, a correlation is found between δ30Si and Ca/Si. This is consistent with the measured basaltic composition and indicates isotopic fractionation during Si removal from the dissolved phase. By calculating the fraction of Si that is removed from the dissolved phase into secondary phases it is possible to use the riverine Si flux (Si denudation rate) to calculate the initial dissolution rate of Si within these catchments. From this study we estimate that the total amount of Si being dissolved by primary weathering of Iceland is 3 million tons per yr. However only ∼ 50% of this Si is released into the rivers and contributes to denudation. Using the Si isotope composition and the Si fraction removed, it is possible to model the Si isotope fractionation as either a Rayleigh-type fractionation or a steady-state system. Both yield similar fractionation factors of about - 1.5‰ δ30Si, implying only one underlying fractionation process that is controlled by external parameters, such as runoff. Furthermore, rivers that follow a steady-state fractionation model are associated with higher Si dissolution rates and lower δ30Si values, indicating an inverse relationship between weathering rates and dissolved riverine Si isotope composition. © 2007 Elsevier B.V. All rights reserved.